Pengembangan Moral Force Aktivis Badan Eksekutif Mahasiswa Sekolah Tinggi Agama Buddha Negeri Sriwijaya - Tyas Nurmaya Dewi (STABN Sriwjaya, 2023)
This research is a descriptive qualitative research that aims to describe the form of moral force development for activists of the Student Executive Board of STABN Sriwijaya Tangerang Banten. This research was conducted in Tangerang involving the subject of BEM STABN Sriwijaya Tangerang Banten activists. The selection of subjects was carried out using the snowball throwing method. The research data were collected using observation, interview, and documentation study methods. The research data were analyzed by referring to the Miles Huberman data analysis model which consists of data reduction, data presentation, and conclusion drawing stages. The results showed that activists of BEM STABN Sriwijaya have a good moral force because they have been able to be responsible for their duties and obligations, disciplined, and become role models for other students. The obstacles faced in developing the moral force of BEM STABN Sriwijaya activists include (1) still not having the courage to try new things, (2) the existence of unfavorable influences from associations and social media, and (3) time constraints because they have to divide lectures and organizations well. The development of moral force has a positive impact on the academic ability, social life, and career life of BEM STABN Sriwijaya activists.